Lattice Boltzmann simulations of contact line motion. I. Liquid-gas systems. - Briant, A; Wagner, A; Yeomans, J (2004)
We investigate the applicability of a mesoscale modeling approach, lattice Boltzmann simulations, to the problem of contact line motion in one and two component, two phase fluids. In this, the first of two papers, we consider liquid-gas systems. Careful implementation of the thermodynamic boundary condition allows us to fix the static contact angle in the simulations. We then consider the behavior of a sheared interface. We show that the contact line singularity is overcome by evaporation or condensation near the contact line which is driven by the curvature of the diffuse interface. An analytic approximation is derived for the angular position of a sheared interface.